Beating Heart: An Innovative Approach to Valve Replacement in Severe Heart Failure - U. T. Khayrullaev; G. U. Mullabaeva; I. M. Sharipov; Sh. N. Doniyorov; Kh. G. Fozilov (International Journal of Biomedicine)
Patients with heart failure with reduced ejection fraction (HFrEF) and valvular heart disease present a significant challenge for both cardiac surgeons and cardiologists. The high risk of heart failure progression associated with traditional surgeries, especially when using CPB, often leads to the refusal of surgical interventions, leaving patients with limited treatment options. One alternative is performing surgeries on a “beating heart” without stopping the heart or using cardioplegia; however, data on the safety and outcomes of this method remain limited. This article presents a clinical case of mitral and aortic valve replacement using the BH technique with retrograde myocardial perfusion in a patient with severe HFrEF. In this clinical case, the beating heart method demonstrated its effectiveness and safety in performing two-valve replacement in a patient with CHF and significantly reduced LVEF. Retrograde perfusion provided adequate myocardial protection, minimizing ischemic damage and contributing to a successful outcome.